Audit committee and value relevance of accounting Information of listed hotels and travels in Sri Lanka - Balagobei, S. (Macrothink Institute, 2017)
The audit committee (AC) is the potential mechanism that reduces the agency problems in organizations and investigating this mechanism separate from alternate corporate governance mechanisms may have led to different results in the literature. The aim of this study is to examine the impact of audit committee on value relevance of accounting information of listed hotels and travels in Sri Lanka. Value relevance of accounting information is measured by earning per share (EPS) and book value per share (BVPS) while Audit committee consists of AC size, AC independence, AC experts and AC meetings. The sample consists of 15 hotels and travels listed in Colombo Stock Exchange. In this study, data was collected from secondary sources and hypotheses are examined by using Pearson’s correlation and regression analysis. The results reveal that audit committee attributes such as AC size, AC experts and AC meetings have a significant impact on book value per share of listed hotels and travels in Sri Lanka. Further only AC experts influence earnings per share. AC independence is not found to have a significant impact on the value relevance of accounting information. The findings could be useful to regulators in other jurisdiction who are looking at ways to enhance the effectiveness of audit committee, overall firm governance.
Keywords: Audit Committee; Value relevance of Accounting information; Audit committee size; Audit committee experts; Audit committee meetings